2021
DOI: 10.3390/covid1030046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2 Antigen Tests in Asymptomatic Testing of Passengers at German Airports under Time Constraints: Application of Three Different Antigen Test Formats

Abstract: People infected asymptomatically with SARS-CoV-2 can spread the virus very efficiently. To break infection chains, massive testing efforts are underway. While the value of RT-PCR in asymptomatic patients is established, point-of-care (POC) antigen tests against SARS-CoV-2 are considered inferior to RT-PCR in terms of sensitivity and specificity but have demonstrated utility, mostly in symptomatic patients. We compared the performance of three different antigen tests with colorimetric (Roche), fluorometric (Qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Scale-up of testing can prevent the spread and tackle the pandemic. As shown in Tables 3 and 4, the sensitivity of the DIAGNOVIR rapid test was found to be 100% among asymptomatic patients, and it was 97.5%, 48.1%, 48.1% and 71.43% for the Lumipulse, Panbio, SD Biosensor, and Roche, respectively [33][34][35][36] . Some studies suggested that the peak of transmissibility is at or even before the time of symptom onset.…”
Section: Discussionmentioning
confidence: 96%
“…Scale-up of testing can prevent the spread and tackle the pandemic. As shown in Tables 3 and 4, the sensitivity of the DIAGNOVIR rapid test was found to be 100% among asymptomatic patients, and it was 97.5%, 48.1%, 48.1% and 71.43% for the Lumipulse, Panbio, SD Biosensor, and Roche, respectively [33][34][35][36] . Some studies suggested that the peak of transmissibility is at or even before the time of symptom onset.…”
Section: Discussionmentioning
confidence: 96%